[tex] \frac{1}{3}[ \frac{1}{3} [ \frac{1}{3} ( \frac{x}{3} +1)+3]+1]+3=4 [/tex]
[tex]\frac{1}{3}[ \frac{1}{3} [ \frac{1}{3} ( \frac{x}{3} +1)+3]+1] = 4-3=1[/tex]
[tex]\frac{1}{3} [ \frac{1}{3} ( \frac{x}{3} +1)+3]+1] = 3*1=3[/tex]
[tex]\frac{1}{3} [ \frac{1}{3} ( \frac{x}{3} +1)+3]=3-1 = 2[/tex]
[tex]\frac{1}{3} ( \frac{x}{3} +1)+3]=2*3=6[/tex]
[tex]\frac{1}{3} ( \frac{x}{3} +1)=6-3=3[/tex]
[tex]\frac{x}{3} +1=3*3=9[/tex]
Dupa ce scazi pe rand termenii adunati la finalul ecuatiei si inmultesti cu 3 tot pe rand ajungi la ecuatia:
x/3 +1=9
[tex]x=(9-1)*3=24[/tex]